The impact of comorbid gastroesophageal reflux disease on endoscopic sinus surgery quality-of-life outcomes - DeConde, Adam S. (2014)
BACKGROUND: Chronic rhinosinusitis (CRS) and gastroesophageal reflux disease (GERD) are common entities that overlap in patient demographics. The pathophysiologic role of GERD has yet to be elucidated, but it is postulated the extra-esophageal reflux may contribute to worsening symptoms of CRS. This study seeks to investigate whether patients with CRS with and without a history of GERD experience comparable quality-of-life (QOL) improvement after endoscopic sinus surgery (ESS). METHODS: An adult cohort (n=229) with medically refractory CRS was prospectively assessed following ESS using three disease-specific QOL constructs. A patient subset with a history of comorbid GERD was retrospectively identified (n=72) and preoperative and postoperative QOL were compared to patients without GERD (n=157). RESULTS: Patients with comorbid GERD and CRS were comparable across all baseline patient characterstics (p>0.050) with the exception of patients with a history of GERD were less likely to have undergone allergy testing (p<0.002) and were older (53.8 years vs. 47.6; p<0.002). Similarly, baseline objective and subjective measures of disease were comparable between patients with CRS with and without GERD (p>0.050). Both groups experienced significant QOL improvement across all QOL constructs (p<0.021), and no difference was detected in the magnitude of that improvement between patients with and without a history of GERD (p>0.050). Similarly, patients on active medical therapy for GERD (n=49) had QOL gains comparable to patients not reporting GERD medical therapy (p>0.050). CONCLUSIONS: Patients electing ESS for CRS with and without comorbid GERD have comparable baseline characteristics and QOL outcomes following surgery.